(untitled) (Memorias Sifored - Encuentros Educación UAN, 2022)
Working and strengthening scientific skills from the first grades of elementary school, bring benefits to the students in the perception and understanding of their context and prepares them, to be critical agents in the face of what happens around them. It is for the above, that this research is carried out, seeking to strengthen scientific skills from the development and application of a diagnostic test that allows us to identify the level of second grade students, group 201 of an official institution from the south of Bogotá, Colombia. The methodology was carried out in three phases: the elaboration of the diagnostic test, the validation of the instrument and its application. The partial results obtained through this, reveals that children are not using scientific skills due to the lack of their own activities to develop and strengthen the different scientific skills that are approached when they work on Natural Sciences in the school context.